Lipid Droplet Metabolism during Dengue Virus Infection. Issue 8 (August 2018) - Randall, Glenn
Abstract : Dengue virus (DENV) induces a proviral selective autophagy targeting lipid droplets, termed lipophagy, that stimulates lipid metabolism. Zhang et al . gained mechanistic insight into this process, demonstrating that DENV NS4A/B binds unmodified AUP1 and promotes its translocation from lipid droplets to autophagosomes to drive the induction of lipophagy.